A sbc polymer, a preparation method thereof and a method for toughening waste plastic
Patent Information
- Application Number
- CN202210453535.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-27
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-04-27
AI Technical Summary
[0005]现有这些增韧改性回收塑料的技术中主要有通过接枝化学改性、加入特种增韧剂等方式,存在工艺复杂、流程长、成本高等缺点
[0037]本发明的技术方案提供的回收塑料增韧用SBC聚合物,由于特殊的组成和结构,不仅对回收塑料具有很好的增韧效果(每100份回收塑料中加入所述SBC聚合物5~10份,韧性提高20%以上),且能进行切粒工艺,物理形态呈细颗粒状,使用便捷,提高了生产效益。相比现有了化学改性、加入特种增韧剂等方式,方法简单、流程短、成本低且适用所有的回收塑料。
Smart Images

Figure BDA0003619807290000071 
Figure BDA0003619807290000081 
Figure BDA0003619807290000091
Abstract
Description
Technical Field
[0001] This invention relates to a toughened rubber, particularly to an SBC polymer for toughening waste plastics, and also to its preparation method and a method for toughening waste plastics, belonging to the field of toughening technology for recycled plastics. Background Technology
[0002] The general public refers to plastics with large production volumes, low prices, wide applications, and broad impact as general-purpose plastics. There are five main types of general-purpose plastics: polyethylene, polypropylene, polyvinyl chloride, polystyrene, and acrylonitrile-butadiene-styrene copolymer (ABS). my country is the world's largest producer and consumer of plastics, accounting for one-third of global production. Data shows that from 2015 to 2021, with rapid economic development, my country's annual production of plastic products exceeded 60 million tons. Large-scale production and use of plastic products inevitably generate a large amount of waste plastic over time. Properly disposing of waste plastic is a pressing issue for my country. Since 2013, with increasing environmental awareness, the amount of waste plastic recycled in China has gradually increased. From 2015 to 2019, my country's waste plastic recycling volume showed an overall upward trend. In 2019, the amount of waste plastic recycled was approximately 18.9 million tons, a year-on-year increase of 3.3%. However, due to the high production volume of plastic products in my country in 2019, the recycling rate of waste plastic was low, at only 23.09%.
[0003] In recent years, the recycling and reuse of waste plastics has become a major research hotspot. Currently, the main recycling and treatment methods are as follows: (1) Mechanical recycling can be further divided into simple recycling and modified recycling; (2) Chemical recycling can be further divided into direct incineration and chemical decomposition, among which chemical decomposition is divided into pyrolysis, water / alcohol cracking and hydrocracking, fluidized catalytic cracking and hydrocracking.
[0004] Chinese patent (CN 106928529A) discloses a high-toughness composite recycled plastic, which is made from the following raw materials in parts by weight: 100 parts waste plastic, 10-16 parts calcium borate, 30-50 parts filler, 0.5-1.5 parts antioxidant, 10-30 parts toughening agent, 3-6 parts N,N'-methylenebisacrylamide, and 6-10 parts reinforcing agent. This invention, through the synergistic effect of multiple raw materials, not only improves the compatibility and dispersibility of the raw materials, but also significantly enhances the strength and toughness of the composite recycled plastic. It is odorless, low in toxicity, environmentally friendly, and has an extended service life, thereby reducing production and usage costs. Chinese patent (CN 110527234A) discloses a method of using acrylic acid, maleic anhydride, and other monomers as monomers, and performing grafting modifications to varying degrees in a reaction vessel to form monomer mixtures with good compatibility. This results in plastics with excellent toughness and resistance to cracking. The added dopamine solution undergoes oxidative self-polymerization under weakly alkaline conditions, acting as a strong adhesive between components through covalent, non-covalent, and hydrogen bonds, improving internal stability. The subsequent addition of graphene oxide, with its large specific surface area and carboxyl groups, allows it to be electrostatically adsorbed onto the positively charged polyelectrolyte surface, reinforcing the multilayer network structure and significantly improving toughness, thus reducing the likelihood of cracking. This invention solves the problem of commonly used plastic toughening agents exhibiting high brittleness and susceptibility to cracking under external forces. Chinese Patent (CN 111269527A) discloses a waste plastic recycling material, recycled product, and recycling method thereof. The waste plastic recycling material is prepared from raw materials comprising the following components in the indicated weight proportions: 65-75 parts waste plastic and 5-15 parts virgin plastic as the base material; 5-15 parts stone powder, 5-15 parts glass fiber powder, and 0-5 parts straw powder as fillers; and 1-5 parts lubricant, 1-5 parts stabilizer, 2-5 parts compatibilizer, 2-4 parts toughening agent, 1-3 parts antioxidant, 3-8 parts coupling agent, 1-2 parts titanium dioxide, 0.5-1 part zirconium oxide, and 1-2 parts camphor oil as additives. The above raw materials are processed through melting, mixing, stirring, cooling, and molding to obtain the recycled plastic product. This invention is applicable to the recycling of various types of waste plastics, effectively improving the comprehensive performance of recycled plastics. The finished product has an extremely wide range of applications, and the recycling process is simple, with low production costs and easy promotion.Chinese Patent (CN 112143163A) discloses a method for toughening and modifying ABS plastic used for lead-acid battery casings. This method modifies ABS recycled material by adding high-polymer ABS powder, silane coupling agent, white oil, and antioxidant. The addition of high-polymer ABS powder alters the tensile strength, elongation at break, impact resistance, heat distortion temperature, and melt flow index of the recycled ABS. This allows for the enhancement or reduction of the properties of the recycled ABS plastic according to production needs, expanding the application range of recycled ABS plastic and enabling effective treatment of waste ABS plastic. Chinese Patent (CN 112391026A) discloses a method for reinforcing and toughening recycled ABS coordination crosslinking materials and its preparation, belonging to the field of recycled ABS material modification technology. It is mainly composed of the following components in parts by weight: 100 parts of recycled ABS resin, 1-20 parts of transition metal salt, and 1-15 parts of toughening agent. The recycled ABS coordination crosslinking material prepared by it has good mechanical properties and toughness. The tensile strength, flexural strength, modulus and impact strength of recycled ABS plastic are significantly improved, and the processing performance of the material is improved.
[0005] The existing technologies for toughening and modifying recycled plastics mainly involve grafting chemical modification and adding special toughening agents, but these technologies have drawbacks such as complex processes, long procedures, and high costs. Summary of the Invention
[0006] To address the technical problems existing in the prior art, the first objective of this invention is to provide an SBC polymer composed of a blend of an SBR polymer containing microblocks and a coupled linear double-arm SBS polymer with a high content of diblocks. This SBC polymer not only has a good toughening effect on waste plastics, but also can be pelletized, and its physical form is fine granules, thus having broad application prospects.
[0007] Another objective of this invention is to provide a method for preparing SBC polymers, which can be achieved using traditional anionic polymerization and has advantages such as simple operation, mild conditions, and low cost.
[0008] The third objective of this invention is to provide a toughening method for waste plastics, which uses SBC polymer to toughen waste plastics. This method not only has a good toughening effect (adding 5-10 parts of SBC polymer to every 100 parts of recycled plastic increases toughness by more than 20%), but also allows for pelletizing, improving production efficiency. Compared with existing toughening methods such as chemical modification and the addition of special toughening agents, this method is simple to operate, has a short process, low cost, and is applicable to all recycled plastics.
[0009] To achieve the above-mentioned technical objectives, the present invention provides an SBC polymer for toughening waste plastics, which is formed by physical blending of SBR polymer and SBS polymer.
[0010] The SBC polymer provided by this invention is formed by physical blending of an SBR polymer containing styrene microblocks and a coupled linear double-arm SBS polymer with high diblock content to form an SBC polymer with a wide distribution of styrene microregions. This polymer exhibits good toughening properties for waste plastics and also has good processing performance.
[0011] As a preferred embodiment, the SBR polymer has a block weight ratio (S / B) of 25 / 75 to 50 / 50 and a number-average molecular weight of 70,000 to 150,000. As a more preferred embodiment, the SBR polymer has a block weight ratio (S / B) of 30 / 65 to 50 / 50 and a number-average molecular weight of 80,000 to 120,000. Controlling the styrene content in the SBR polymer within the preferred range allows for better control of its randomness above 80%. Higher randomness results in a more uniform distribution of stress concentration points during SBR polymer toughening of recycled plastics, leading to better toughening effects. Controlling the molecular weight of the SBR polymer within the preferred range ensures a moderate overall polymer viscosity, resulting in better processability and easier pelletizing. When the S / B block ratio of the SBR polymer is too high, the butadiene blocks in the SBR molecular chain are small, leading to fewer stress concentration points during plastic toughening and affecting the toughening effect. However, if the block ratio is too low, fewer styrene microblocks are formed in the molecular chain, affecting subsequent pelletizing and grinding processes.
[0012] As a preferred embodiment, the SBS polymer is a linear two-arm SBS polymer formed by the coupling of diblock SB polymers, wherein the S / B weight ratio is 20 / 80 to 45 / 55, the number-average molecular weight of the diblock SB is 80,000 to 150,000, and the coupling rate of the diblock SB is 10% to 50%. In a further preferred embodiment, the SBS polymer is a coupled linear two-arm SB polymer, with an S / B weight ratio of 20 / 80 to 35 / 65, the number-average molecular weight of the diblock SB is 100,000 to 140,000, and the coupling rate of the diblock SB is 20% to 30%. If the molecular weight of each arm is too large, the coupling efficiency will be too low; conversely, if the molecular weight of each arm is too low, the mechanical properties of the linear two-arm SBS polymer will be poor, affecting the toughening effect of the SBS polymer in plastic applications. The coupling rate of the diblock SB refers to the molar percentage of diblock SB that participated in the coupling reaction.
[0013] As a preferred embodiment, the mass ratio of the SBR polymer to the SBS polymer is 50 / 50 to 80 / 20. As a more preferred embodiment, the mass ratio of the SBR polymer to the SBS polymer is 55 / 45 to 75 / 25. Within this range, the SBR polymer not only exhibits good toughening effects but also meets the viscosity requirements of the pelletizing process.
[0014] This invention also provides a method for preparing an SBC polymer for toughening waste plastics, comprising the following steps:
[0015] 1) In an anionic polymerization system, styrene is first added for a first-stage polymerization, then butadiene is added for a second-stage polymerization. After the second-stage polymerization is completed, a linear coupling agent is added for a coupling reaction to obtain SBS adhesive.
[0016] 2) In an anionic polymerization system, SBR adhesive is obtained by copolymerizing styrene and butadiene mixed monomers through continuous addition;
[0017] 3) After the SBS and SBR adhesives are thoroughly mixed, they are successively coagulated, pelletized, and dried to obtain the SBC polymer.
[0018] As a preferred embodiment, the polymerization process is carried out at a temperature of 50–60°C for 20–40 minutes.
[0019] As a preferred embodiment, the two-stage polymerization process is carried out at a temperature below 100°C for a time of 20–40 minutes.
[0020] As a preferred embodiment, the coupling reaction is carried out at a temperature of 50–60°C for a duration of 20–40 minutes.
[0021] As a preferred embodiment, during the copolymerization process, the styrene and butadiene mixed monomers are continuously added over a period of 20–40 minutes, at a temperature of 60–65°C, for a duration of 60–90 minutes. Continuous feeding can improve the randomness of the styrene-butadiene polymerization.
[0022] As a preferred embodiment, the linear coupling agent is dichlorodimethylsilane; the amount of the linear coupling agent added is 5% to 25% of the initiator mass.
[0023] The present invention also provides a method for toughening waste plastics, wherein the SBC polymer is mixed with waste plastics and vulcanized.
[0024] As a preferred embodiment, the mass ratio of the SBC polymer to waste plastic is 5 to 10:100.
[0025] As a preferred embodiment, the anionic polymerization system includes a nonpolar organic solvent, an initiator, and an activator.
[0026] As a preferred embodiment, the nonpolar organic solvent includes at least one of straight-chain alkanes (such as n-hexane), cycloalkanes (such as cyclohexane), and benzene. The amount of nonpolar organic solvent added is conventional, generally ensuring that the total mass of the polymerized monomers accounts for 5-15% of the solvent mass.
[0027] As a preferred embodiment, the activator comprises tetrahydrofuran, and a trace amount of the activator initiates the dissociation reaction of the initiator n-butyllithium. n-Butyllithium has high reactivity and typically exists in the form of an associative compound.
[0028] As a preferred embodiment, the initiator comprises n-butyllithium. The amount of initiator added is related to the molecular weight of the target molecule and is added according to the actual situation, which is common knowledge in the art.
[0029] The SBC polymer of the present invention can be obtained by the following method:
[0030] (1) Synthesis method of SBS polymer
[0031] A metered amount of solvent, styrene, and activator (e.g., tetrahydrofuran) are added to a reactor (polymerization reactor). At a reactor temperature of 50–60°C, a metered amount of initiator (e.g., n-butyllithium) is added. The reaction is allowed to proceed for 30 minutes. After the reaction is complete, butadiene is added at a reactor temperature of 50–60°C for a two-stage polymerization, with the reaction temperature controlled below 100°C. The reaction is allowed to proceed for another 30 minutes. After the reaction is complete, a linear coupling agent is added at a reactor temperature of 50–60°C for a coupling reaction of 20–40 minutes. The SBS polymer is then obtained upon completion of the reaction.
[0032] (2) Synthesis methods of SBR polymers
[0033] A metered solvent and activator (e.g., tetrahydrofuran) are added to a reaction vessel (polymerization vessel). At a vessel temperature of 60–65°C, a metered initiator (e.g., n-butyllithium) is added. A metered styrene / butadiene monomer is added using a continuous feeding method. The feeding time is controlled at 20–40 minutes, and the reaction time is 60–90 minutes. After the reaction is completed, the SBR polymer is obtained.
[0034] (3) Synthesis methods of SBC polymers
[0035] The SBS and SBR obtained by (1) and (2) respectively are pressed into a mixing tank, and after being thoroughly stirred, they are subjected to processes such as aqueous coagulation, pelletizing, and drying to obtain the SBC polymer.
[0036] Compared with the prior art, the technical solution of the present invention brings the following beneficial technical effects:
[0037] The SBC polymer for toughening recycled plastics provided by this invention, due to its special composition and structure, not only has a good toughening effect on recycled plastics (adding 5-10 parts of the SBC polymer to every 100 parts of recycled plastic increases toughness by more than 20%), but also allows for pelletizing, resulting in fine granules that are easy to use and improve production efficiency. Compared with existing methods such as chemical modification and the addition of special toughening agents, this method is simple, has a short process, low cost, and is applicable to all recycled plastics.
[0038] The method for preparing the SBC polymer of the present invention can be achieved by using the classic anionic polymerization method, which has the advantages of simple operation, mild conditions and low cost. Detailed Implementation
[0039] To further illustrate the details of the present invention, several embodiments are provided. These embodiments are intended to explain the content of the invention, and not to limit the scope of protection of the claims.
[0040] Analytical methods: Molecular weight and molecular weight distribution were determined by gel permeation chromatography; melt index was tested according to ASTM D1238; tensile strength was tested according to GB / T 1040.2-2006; impact strength was tested according to GB / T 1843-2008.
[0041] Example 1
[0042] (1) Synthesis of SBR:
[0043] 2400 g of cyclohexane and 0.1 g of activator were added to the polymerization reactor. 3 mmol of n-butyllithium was added at 60 °C. The styrene / butadiene monomer mixture (styrene: 135 g, butadiene: 165 g) was then continuously added to the mixing tank. The addition time was controlled at 30 minutes, the maximum reaction temperature was controlled below 95 °C, and the reaction time was controlled at 80 minutes. After the reaction was completed, samples were taken for gel permeation chromatography analysis. Finally, the remaining gel solution was placed in an enamel bucket for later use. The gel permeation chromatography analysis results are shown in Table 1.
[0044] Table 1 SBR structural parameters
[0045]
[0046] (2) Synthesis of SBS
[0047] 2400g of cyclohexane, 52g of styrene, and 0.1g of activator were added to a polymerization reactor. 2.08mmol of n-butyllithium was added at 55℃, and the reaction was allowed to proceed for 30 minutes. After the monomers had completely reacted, 208g of butadiene was added, and the reaction temperature was controlled below 100℃. The reaction was allowed to proceed for another 30 minutes. After the monomers had completely reacted, 0.027g of dichlorodimethylsilane, a linear coupling agent, was added, and the reaction was allowed to proceed for another 30 minutes at 55℃. After the reaction was complete, a sample was taken to determine the molecular weight and molecular weight distribution. Finally, the remaining gel solution was placed in an enamel bucket for later use. The gel permeation chromatography analysis results are shown in Table 2.
[0048] Table 2 SBS structural parameters
[0049]
[0050] (3) The SBR obtained in (1) and the SBS obtained in (2) are placed in an enamel bucket and stirred thoroughly. After being mixed evenly, the mixture is washed, coagulated, and dried to obtain SBC polymer for toughening recycled plastics. The mass ratio of SBR to SBS is 75:65.
[0051] (4) Weigh 100g of recycled plastic and 10g of SBC polymer. Perform intensive mixing using a torque rheometer. After mixing, vulcanize the mixture into sheets using a plate vulcanization process. Evaluate the relevant physical properties after completion. The results are shown in Table 3.
[0052] Table 3 Properties of Toughened Plastics
[0053] Before toughening recycled plastic 30.6 12.0 26.0 Toughened recycled plastic 40.8 15.7 21.7
[0054] Note: The test conditions for melt flow index are: 190℃, 5.0kg.
[0055] Example 2
[0056] (1) Synthesis of SBR
[0057] 2400g of cyclohexane and 0.1g of activator were added to the polymerization reactor. 3mmol of n-butyllithium was added at 60℃. The styrene / butadiene monomer mixture (styrene: 135g, butadiene: 165g) was then continuously added to the mixing tank. The addition time was controlled at 30 minutes, the maximum reaction temperature was controlled below 95℃, and the reaction time was controlled at 80 minutes. After the reaction was completed, samples were taken for gel permeation chromatography analysis. Finally, the remaining gel solution was placed in an enamel bucket for later use. The gel permeation chromatography analysis results are shown in Table 4.
[0058] Table 4 SBR structural parameters
[0059]
[0060] (2) Synthesis of SBS
[0061] 2400g of cyclohexane, 60g of styrene, and 0.1g of activator were added to a polymerization reactor. 2.6mmol of n-butyllithium was added at 55℃, and the reaction was allowed to proceed for 30 minutes. After the monomers had completely reacted, 240g of butadiene was added, and the reaction temperature was controlled below 100℃. The reaction was allowed to proceed for another 30 minutes. After the monomers had completely reacted, 0.034g of dichlorodimethylsilane, a linear coupling agent, was added, and the reaction was allowed to proceed for another 30 minutes at 55℃. After the reaction was complete, a sample was taken to determine the molecular weight and molecular weight distribution. Finally, the remaining gel solution was placed in an enamel container for later use. The results of gel permeation chromatography analysis are shown in Table 5.
[0062] Table 5 SBS structural parameters
[0063]
[0064] (3) The SBR obtained in (1) and the SBS obtained in (2) are placed in an enamel bucket and stirred thoroughly. After being mixed evenly, the mixture is washed with water, coagulated, and dried to obtain SBC polymer for toughening recycled plastics. The mass ratio of SBR to SBS is 50:50.
[0065] (4) Weigh 100g of recycled plastic and 10g of SBC polymer. Mix them using a torque rheometer. After mixing, vulcanize them into sheets using a plate vulcanization process. The relevant physical properties were then evaluated. The results are shown in Table 6.
[0066] Table 6 Toughening Properties of Plastics
[0067] Before toughening recycled plastic 29.0 10.8 20.6 Toughened recycled plastic 35.8 13.0 19.3
[0068] Note: The test conditions for melt flow index are: 190℃, 5.0kg.
[0069] Example 3
[0070] (1) Synthesis of SBR;
[0071] 2400 g of cyclohexane and 0.1 g of activator were added to the polymerization reactor. 3 mmol of n-butyllithium was added at 60°C. The styrene / butadiene monomer mixture (90 g styrene, 210 g butadiene) was then continuously added to the mixing tank. The addition time was controlled at 30 minutes, the maximum reaction temperature was controlled below 95°C, and the reaction time was controlled at 80 minutes. After the reaction was complete, samples were taken for gel permeation chromatography analysis. Finally, the remaining gel solution was placed in an enamel bucket for later use. The gel permeation chromatography analysis results are shown in Table 7.
[0072] Table 7 SBR Structural Parameters
[0073]
[0074] (2) Synthesis of SBS
[0075] 2400g of cyclohexane, 78g of styrene, and 0.1g of activator were added to a polymerization reactor. 2.08mmol of n-butyllithium was added at 55℃, and the reaction was allowed to proceed for 30 minutes. After the monomers had completely reacted, 182g of butadiene was added, and the reaction temperature was controlled below 100℃. The reaction was allowed to proceed for another 30 minutes. After the monomers had completely reacted, 0.027g of dichlorodimethylsilane, a linear coupling agent, was added, and the reaction was allowed to proceed for another 30 minutes at 55℃. After the reaction was complete, a sample was taken to determine the molecular weight and molecular weight distribution. Finally, the remaining gel solution was placed in an enamel container for later use. The results of gel permeation chromatography analysis are shown in Table 8.
[0076] Table 8 SBS structural parameters
[0077]
[0078]
[0079] (3) The SBR obtained in (1) and the SBS obtained in (2) are placed in an enamel bucket and stirred thoroughly. After being mixed evenly, the mixture is washed with water, coagulated, and dried to obtain SBC polymer for toughening recycled plastics. The mass ratio of SBR to SBS is 75 / 65.
[0080] (4) Weigh 100g of recycled plastic and 10g of SBC polymer. Perform intensive mixing using a torque rheometer. After mixing, vulcanize the mixture into sheets using a plate vulcanization process. Evaluate the relevant physical properties after completion. The results are shown in Table 9.
[0081] Table 9 Toughening Properties of Plastics
[0082] Before toughening recycled plastic 30.6 12.0 26.0 Toughened recycled plastic 40.1 16.1 21.6
[0083] Note: The test conditions for melt flow index are: 190℃, 5.0kg.
[0084] Comparative Example 1
[0085] (1) Synthesis of SBR;
[0086] 2400 g of cyclohexane and 0.1 g of activator were added to the polymerization reactor. 3 mmol of n-butyllithium was added at 60 °C. The styrene / butadiene monomer mixture (styrene: 180 g, butadiene: 120 g) was then continuously added to the mixing tank. The addition time was controlled at 30 minutes, the maximum reaction temperature was controlled below 95 °C, and the reaction time was controlled at 80 minutes. After the reaction was completed, samples were taken for gel permeation chromatography analysis. Finally, the remaining gel solution was placed in an enamel bucket for later use. The gel permeation chromatography analysis results are shown in Table 10.
[0087] Table 10 SBR Structural Parameters
[0088]
[0089]
[0090] (2) Synthesis of SBS
[0091] 2400g of cyclohexane, 60g of styrene, and 0.1g of activator were added to a polymerization reactor. 2.6mmol of n-butyllithium was added at 55℃, and the reaction was allowed to proceed for 30 minutes. After the monomers had completely reacted, 240g of butadiene was added, and the reaction temperature was controlled below 100℃. The reaction was allowed to proceed for another 30 minutes. After the monomers had completely reacted, 0.034g of dichlorodimethylsilane, a linear coupling agent, was added, and the reaction was allowed to proceed for another 30 minutes at 55℃. After the reaction was complete, a sample was taken to determine the molecular weight and molecular weight distribution. Finally, the remaining gel solution was placed in an enamel bucket for later use. The results of gel permeation chromatography analysis are shown in Table 11.
[0092] Table 11 SBS structural parameters
[0093]
[0094] (3) The SBR obtained in (1) and the SBS obtained in (2) are placed in an enamel bucket and stirred thoroughly. After being mixed evenly, the mixture is washed with water, coagulated, and dried to obtain SBC polymer for toughening recycled plastics. The mass ratio of SBR to SBS is 50:50.
[0095] (4) Weigh 100g of recycled plastic and 10g of SBC polymer. Perform intensive mixing using a torque rheometer. After mixing, vulcanize the mixture into sheets using a plate vulcanization process. Evaluate the relevant physical properties after completion. The results are shown in Table 12.
[0096] Table 12 Toughening Properties of Plastics
[0097] Before toughening recycled plastic 28.6 10.8 19.6. Toughened recycled plastic 31.5 11.6 19.2
[0098] Note: The test conditions for melt flow index are: 190℃, 5.0kg.
Claims
1. An SBC polymer for toughening waste plastics, characterized in that: It is made by physical blending of SBR polymer and SBS polymer; The block weight ratio of the SBR polymer is S / B = 25 / 75~50 / 50, and the number average molecular weight is 70,000~150,000. The SBS polymer is a linear two-arm SBS polymer formed by coupling diblock SB polymers, wherein the S / B weight ratio is 20 / 80 to 45 / 55, the number average molecular weight of the diblock SB is 80,000 to 150,000, and the coupling rate of the diblock SB is 10% to 50%. The mass ratio of the SBR polymer to the SBS polymer is 50 / 50 to 80 / 20.
2. The SBC polymer for toughening waste plastics according to claim 1, characterized in that: The SBR polymer has a block weight ratio of S / B = 30 / 65 to 50 / 50 and a number average molecular weight of 80,000 to 120,000.
3. The SBC polymer for toughening waste plastics according to claim 1, characterized in that: The SBS polymer has an S / B weight ratio of 20 / 80 to 35 / 65, a number-average molecular weight of 100,000 to 140,000 for the diblock SB, and a coupling rate of 20% to 30% for the diblock SB.
4. The SBC polymer for toughening waste plastics according to claim 1, characterized in that: The mass ratio of the SBR polymer to the SBS polymer is 55 / 45 to 75 / 25.
5. A method for preparing an SBC polymer for toughening waste plastics according to any one of claims 1 to 4, characterized in that: Includes the following steps: 1) In an anionic polymerization system, styrene is first added for a first-stage polymerization, then butadiene is added for a second-stage polymerization. After the second-stage polymerization is completed, a linear coupling agent is added for a coupling reaction to obtain SBS adhesive. 2) In an anionic polymerization system, SBR adhesive is obtained by copolymerizing styrene and butadiene mixed monomers through continuous addition; 3) After the SBS and SBR adhesives are thoroughly mixed, they are successively coagulated, pelletized, and dried to obtain the SBC polymer.
6. The method for preparing an SBC polymer for toughening waste plastics according to claim 5, characterized in that: During the polymerization process, the temperature is 50~60℃ and the time is 20~40 minutes; During the two-stage polymerization process, the temperature is below 100°C and the time is 20-40 minutes; During the coupling reaction, the temperature is 50~60℃ and the time is 20~40 minutes.
7. The method for preparing an SBC polymer for toughening waste plastics according to claim 5, characterized in that: During the copolymerization process, the styrene and butadiene mixed monomers are continuously added for a period of 20 to 40 minutes, at a temperature of 60 to 65°C, and for a duration of 60 to 90 minutes.
8. A method for toughening waste plastics, characterized in that: The SBC polymer described in any one of claims 1 to 5 is mixed and vulcanized with waste plastics.
9. The method for toughening waste plastics according to claim 8, characterized in that: The mass ratio of the SBC polymer to waste plastic is 5~10:100.
Citation Information
Patent Citations
Efficient plastic toughening agent
CN110527234A
Waste plastic regenerated material, regenerated product, and regeneration method thereof
CN111269527A
Toughening modification method of waste lead-acid storage battery shell ABS plastic
CN112143163A
Reinforced and toughened waste recycled ABS coordination crosslinking material and preparation method thereof
CN112391026A
Crosslinked styrenic block copolymer
CN111094406A